Synthesis of Geopolymer-Zeolite Granule Composite from Local Raw Materials Using the Hydrothermal Method as Methylene Blue Adsorbent - Rosida; Abidin, Zaenal; Sri Sugiarti (Jurnal Ilmu Tanah dan Lingkungan, 2024)
Zeolite is known as a cation exchange adsorbent and has high adsorption capabilities. These two functions of zeolite have the opportunity to be a solution in dealing with cationic dye waste. The aim of this research was to determine the CEC value and adsorption capacity of zeolite in adsorbing methylene blue. Zeolite powder is made using local metakaolin and added NaOH or water glass using the hydrothermal method. The powdered zeolite product obtained was mixed with geopolymer to form a composite of small granules and large granules. The results of XRD characterization of the synthetic product obtained from a mixture of metakaolin and NaOH were NaA zeolite, while the addition of water glass resulted in NaX zeolite. Zeolite in powder form or geopolymer-zeolite granule composite shows a high cation exchange capacity (CEC) above 200 cmol/kg. The methylene blue adsorption test on each adsorbent showed that the adsorption capacities of NaA zeolite, NaX zeolite, NaA geopolymer-zeolite small granule and large granule composites, and NaX geopolymer-zeolite small granule and large granule composites were respectively 30.81 mg g-1, 32.84 mg g-1, 53.29 mg g-1, 51.64 mg g-1, 38.32 mg g-1, 54.22 mg g-1 and 48.81 mg g-1.